The role of paid the offices of the Inspectors General on mutation fraud Crimes - جثير سعدون حمود; عذاب ستار مجهول (Journal of Economics and Administrative Sciences, 2014)
Fraud crimes, which is a form of crimes against the funds in public office, is one of the crimes of traditional and cutting-edge in the same time, but it took a distinct character from other traditional crimes because of what is based upon, behavioral fundamentals and foundations and expressive image of personal qualities, concentrated in the mental work, the inventive sophistication, and skillful abilities of the perpetrators of these crimes, in addition to what is owned by crooks today a behavioral ability represented in underestimating laws and instructions. Fraud is considered one of the organized crime methods It is the most important method of its methods, all crimes practiced by the crooks are not free of cheat or deceit or forgery or trick or seduction. The reason for choosing the subject of research is not approving administrative classification for fraud to be based on as standard by procedures of general inspectors offices and to highlight the role of measures in the reduction of these crimes, and from these procedures, provided by the search, are the preventive measures, since the introduction of specialized regulatory (observing) institutions, including the offices of general inspectors, to protect public money and to improve performance of the ministries and the elimination of fraud, waste, and abuse of power and provide better services to citizens, and these devices are of recent origin, it should have the procedures and mechanisms of action commensurate with the increasing of the functional worsening deviations, it must be based on the classification for fraud. And in addition to what this research presented this research from many ideas and points, most notable of which, was the preventive measures, which consists of three coherent, integrated and syndrome pivots one cannot be separated from the other two, the Search named them ( elements of preventive ) These measures are applied by the offices of general inspectors in the implementation of the tasks entrusted to them in order to achieve the objectives and the purpose for which they were created. Those measures were tested on a sample of some of the general inspectors with some assistants and directors of departments and sections in order to test the first hypotheses of the research which were represented in a relationship of a moral sense between measures of general inspector offices and the fraud, in addition to the second main hypothesis which sees that there is an effective relationship of the moral sense in the measures of general inspectors offices. The research has come to the most important conclusions and recommendations that it came out with, including the following: Measures of investigation, checking, inspection, and preventive carried out by the offices of inspectors general (research sample) are done at a very good level in the ministries, which will thereby contribute to the fight and the reduction of fraud that may occur. Results of the statistical analysis of the practical side proved that the offices of general inspectors were in constant contact with all of the reports issued by the authorities and regulatory bodies, and any reliable source of information is not ignored by not dealing with it. The results indicated that the authorities granted to the offices of general inspectors allow them to easily get information from the administrative units which are subject to inspection and easy access to those units without restrictions and this helps a lot the work of general inspectors offices in the elimination of fraud If they make good use of those authorities The preventive measures are the least fragmented in terms of the answers of samples from the rest of the dimensions of the general inspector’s office procedures, which demonstrates the strength and clarity of the preventive measures implemented in the ministries. The results proved that fraud in public office is classified into crimes of corruption and assets fraud and financial disclosure fraud. The results showed that the financial pressure and the opportunity and the justification are some of the important elements in the commission of fraud. The researcher found that the coordination and exchange of information between the offices of general inspectors are important and necessary to reduce fraud. The results proved that the work of the Office of the General Inspector is basically regulatory and preventive and is not a security work as portrayed by some.